How do insiders trade? - Patrick Augustin; Menachem Brenner; Gunnar Grass; Marti G. Subrahmanyam (Goethe University Frankfurt, Center for Financial Studies (CFS), 2016)
We characterize how informed investors trade in the options market ahead of corporate news when they receive private, but noisy, information about (i) the timing of the announcement and (ii) its impact on stock prices. Our theoretical framework generates a rich set of predictions about the insiders' behavior and their maximum expected returns. Three different analyses offer empirical support for our approach. First, predicted trades resemble illegal insider trades documented in SEC litigation cases with insiders being more likely to trade in options that offer higher expected returns. Second, pre-announcement patterns in unusual activity in the options market ahead of significant corporate news are consistent with the predictions of our framework. We employ our approach to characterize informed trading ahead of twelve different types of news including the announcement of earnings, corporate guidance, M&As, product innovations, management changes, and analyst recommendations. Third, to address concerns that pre-announcement patterns are driven by speculation, we show that measures capturing trading activity in call (put) options with high expected returns predict significant positive (negative) corporate news in the aggregate cross-section.
urn:nbn:de:hebis:30:3-416804
Keywords: G12; G13; G14; K42; 330; Insider Trading; Market Microstructure; Corporate Announcements; Extreme Price Movements; Equity Options